A hipovolemia por doação de sangue aumenta a complacência gástrica e eleva o limiar de saciedade em humanos sadios - Macedo, Geraldo Munguba (2010)
Introduction: We have shown that blood shedding reduces tonus and increases gastric compliance in animals. Since satiety to a drinking test is affected by gastric tonus and compliance, we investigated the effect of blood donation (BD) and saline infusion in gastric tonus, compliance and sensitivity in healthy volunteers. Method: After approval of local ethics committee, 23 healthy male volunteers were studied. After an overnight fast (8-10h), followed by a light meal, and a 2h interval, one of the following procedures was performed. Tonus and compliance study. A PVC bag (1.6L) attached to a catheter was placed into the proximal stomach. Gastric volume (GV, ml) was continuously measured by an electronic barostat (Synectics®), with the intrabag pressure fixed at 12mmHg. After 30-min basal recording, the subjects (n=18) were randomly submitted to either BD (450 ml) or venous puncture site manipulation only, and GV was recorded for further 30-min. Small IP increments (until mild pain report) were also performed; before the basal period and at the end of the study. In 5 volunteers, saline infusion (1.3L) was performed 15-min after BD. Satiety. Volunteers were studied in two different occasions, 1 to 2 weeks apart. They were submitted to a blood donation or venous puncture only, before a modified satiety drinking test with a caloric meal was performed. Results: BD caused a rapid increase in GV (values above basal levels: 154 ± 62 ml at 5 minutes after shedding start and 152 ± 66 ml at the end of study, p<0.05). Volume x pressure slope increased (53.7 ± 4.2 vs. 45.1 ± 4.2ml.mmHg-1 basal, P=0.01) after BD. Saline infusion brought GV back to basal levels (0±1 ml basal vs -14 ± 6 ml at 30 min). BD increased the maximum volume ingested by the volunteers (790±56,7 vs. 1327±127ml, p<0.05). The time to reach the maximum score was also increased. (52.8±4 vs. 95.8±8min, p<0.05). The time to elicit the first (beginning to feel full) and third (full) sensations was also increased after BD (19.2±1.3 vs. 41.6 ±4.2min e 37.8±3.5 vs. 67.5 ±6.6min, respectively, p<0.05). BD did not change blood pressure and cardiac rate. Conclusions: BD decreases gastric tonus and increases gastric compliance. Saline infusion reverted such phenomena. Furthermore BD increases the time and volume sensitivity threshold in a satiety drinking test. This might explain dyspeptic complains in individuals under acute volemic imbalance.